Facile synthesis of covalent probes to capture enzymatic intermediates during E1 enzyme catalysis. Issue 12 (17th November 2015) - An, Heeseon; Statsyuk, Alexander V.
Abstract : Electrophilic UBL–AMP probes form a covalent bond with the catalytic cysteine of cognate E1s, mimicking the ternary E1–UBL–AMP intermediates. Abstract : We report a facile synthetic strategy to prepare UBL–AMP electrophilic probes that form a covalent bond with the catalytic cysteine of cognate E1s, mimicking the tetrahedral intermediate of the E1–UBL–AMP complex. These probes enable the structural and biochemical study of both canonical- and non-canonical E1s.